KONSENTRASI ASAM FOSFAT (H3 PO4 ) TERHADAP KARAKTERISTIK ARANG AKTIF KULIT BATANG SAGU - Yen Yen Rahmadini; Vonny Setiaries Johan; MHD Andry Kurniawan (SAGU, 2024)
Activated charcoal is a material that contains 85-95% carbon elements and is a porous solid. This activated charcoal is the result of heating materials containing carbon at high temperatures but does not oxidize. In this research, the materials used were sago bark and the activator was H3PO4. This study aimed to obtain selected characteristics of activated charcoal made from sago bark waste with several concentration of phosphoric acid as an activator. This study was conducted using a complete randomized design with five treatments and three replications. The treatments in this study were variations in H3PO4 concentration, namely H3PO4 5%, H3PO4 7.5%, H3PO4 10%, H3PO4 12.5%, and H3PO4 15%. Observations were made on yield, moisture content, ash content, volatile matter content, bound carbon content and iodine absorption. The data obtained were analyzed statistically analysis of variance (ANOVA) test, and if F count ≥ F table then the treatment has a significant effect and the analysis will be continued with Duncan’s multiple range test (DMRT) at the level of 5%. The results showed that the increase in phosphoric acid concentration used had a significant effect on yield, moisture content, ash content, volatile matter content, bound of carbon content, and absorption of iodine. Activated charcoal with the best treatment was found in treatment H3PO4 activator concentration 15% with a yield of 86.85%, moisture content 1.43%, ash content of 4.77%, volatile matter content 14.10%, bound carbon of content 79.68% and absorption of iodine 837.54 mg/g.